The Internet and Asia-Pacific security: old conflicts and new behaviour. - Otis, Cameron; Evans, Paul (Pacific Review, 2003)
The positive uses of the Internet by civil society groups, research institutes, governments and other entities interested in promoting Asia-Pacific community building and cooperative security regimes have been studied and appreciated. The paper begins with a discussion of regional Internet diffusion patterns and the associated increase in Internet incidents. In the wake of 11 September 2001 and recent analysis of the 'dark side' of the Internet and networks, it then examines some of the destructive ways Internet technologies are being used by actors in the Asia-Pacific region. It provides examples from the patterns of Internet conflict involving a quadral relationship among four nodes, uncivil society, civil society, government and business as well as the pattern of conflict within each of the nodes. Finally, it looks at three topic areas - national security agendas, the making of security policy and the regional security dialogue process - that deserve further attention.